O02.2 Susceptiblity of Bacterial Vaginosis (BV)-Associated Bacteria and Lactobacilli to Rifaximin, Metronidazole and Clindamycin. (13th July 2013) - Hillier, S L; Cosentino, L; Petrina, M; Rabe, L
Abstract : Objective: Rifaximin is a semisynthetic rifamycin with poor oral bioavailability, used as an oral agent for the treatment of traveller's diarrhoea and hepatic encephalopathy. Rifaximin is in development as a topical agent for the treatment of bacterial vaginosis (BV). The objective of this study was to evaluate the antimicrobial susceptibility of vaginal isolates of facultative and anaerobic bacteria to rifaximin, clindamycin and metronidazole. Methods: A total of 411 unique BV-related bacteria and 100 isolates of lactobacilli recovered from the human vagina of US women during the years 2009–2012 were tested for antimicrobial susceptibility by the agar dilution CLSI reference method to calculate MICs. Results: Overall, 142 (35%) of the BV-associated vaginal isolates tested were resistant to metronidazole, 63 (15%) were resistant to clindamycin and 11 (2.6%) were resistant to rifaximin. Metronidazole resistance was observed most frequently among Gardnerella vaginalis (n = 100 isolates, 69% resistant), Atopobium vaginae (n = 62, 87% resistant) and Mobiluncus (n = 40, 42% resistant), whereas most were susceptible to both clindamycin (197/202; 98% susceptible) and rifaximin (191/202; 95% susceptible). Both rifaximin and metronidazole were effective against all strains of Prevotella bivia (n = 34), P timonensis (n = 33), Anaerococcus tetradius (n = 21 ), Finegoldia magna (n = 20) and Peptoniphilus lacrimalis (n = 20), whereas clindamycin resistance was detected among 74%, 42%, 19%, 30% and 30% of these anaerobes isolates, respectively. More than 90% of Prevotella amnii (n = 33), Peptoniphilus harei (n = 23) and Megasphaera -like bacteria (n = 25) were susceptible to all three antibiotics. As expected, none of the Lactobacillus isolates were susceptible to metronidazole, whereas a majority were susceptible to both clindamycin and rifaximin in vitro . Conclusion: Rifaximin had MIC values for a range of microorganisms associated with BV which were superior or similar to the other two drugs approved for the treatment of this condition and deserves clinical evaluation as a new therapeutic agent for the treatment of BV.